Root Finding Methods Through GUI in Spreadsheets: Root Finding Methods Through GUI in Spreadsheets - Razzak, Atteeq; Zaheer, Muhammad Hani; Khan, Muhammad Bilal; Uddin, Zaheer (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
Root finding Methods like the Bisection Method, Newton Raphson Method, Secant Method, and False Position Method have been revisited through a new approach. EACH METHOD’S user-friendly GUI computer programs have been developed on an Excel spreadsheet. A root locator graph is introduced in the spreadsheets, which helps identify the initial guess(es) required to calculate root using these methods. All real roots are now easily calculable by any of the four methods. The detailed steps to calculate roots are also shown on the spreadsheet. The spreadsheet can be made ready for the next calculation with a single click. We have developed a technique for Excel that helps accept polynomial in variable ‘x’ without directly mentioning cell location.